A COMPARISON BETWEEN CLASSIFICATION STATISTICAL MODELS AND NEURAL NETWORKS WITH APPLICATION ON PALESTINE DATA. (2021) - MOHAMED, AMANI MOUSSA; ABDEL-FATTAH, MAHMOUD A.; ALDIRAWI, ABDALLAH SALMAN MOHAMMED
No abstract available